Danshenol B alleviates central post-stroke pain by regulating the PIK3CG/NLRP3 signaling pathway - Panyang Li; Linna Yu; Jinzhong Yao; Tingting Zhao; Sen Zhao (Journal of Translational Medicine, 2025)
Abstract Background Central post-stroke pain (CPSP) is a debilitating neuropathic condition that significantly impairs quality of life and is challenging to manage. Salvia miltiorrhiza (Danshen), a traditional Chinese herb, has demonstrated efficacy against neuropathic pain, but its active analgesic components and underlying mechanisms remain unclear. This study investigated the therapeutic potential of Danshenol B, an active component of Danshen, in a CPSP mouse model, focusing on its mechanism of action via the phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit gamma isoform (PIK3CG)/NLR family pyrin domain-containing protein 3 (NLRP3) signaling pathway. Methods A CPSP model was established in mice, and RNA sequencing of the ipsilateral ventral posterolateral thalamic nucleus/ventral posteromedial thalamic nucleus (VPL/VPM) was performed to identify differentially expressed genes (DEGs). Network pharmacology analysis linked these DEGs to known Danshen components, and molecular docking of 42 Danshen constituents was conducted to identify strong ligand-target interactions. Danshenol B was then administered (5, 10, 50 mg/kg) to CPSP mice to evaluate its analgesic effects, and thalamic PIK3CG and NLRP3 protein levels were measured to assess pathway involvement. Additionally, PIK3CG and NLRP3 expression were manipulated (via overexpression or knockdown) to determine their roles in CPSP and their regulatory relationship. Results In the CPSP model, 409 DEGs were identified in the ipsilateral VPL/VPM. Network pharmacology revealed 21 Danshen-derived compounds potentially targeting 11 of these DEGs. Molecular docking highlighted Danshenol B as a top candidate, showing strong binding (-9.127 kcal/mol) to PIK3CG. In CPSP mice, Danshenol B (50 mg/kg) significantly alleviated CPSP and suppressed the PIK3CG/NLRP3 pathway. The overexpression of PIK3CG increased NLRP3 and negated the effects of Danshenol B, whereas its knockdown alleviated CPSP and reduced NLRP3. Notably, simultaneous overexpression of NLRP3 attenuated the analgesic effects induced by PIK3CG knockdown, further confirming that NLRP3 functions downstream of PIK3CG in mediating CPSP. Conclusions Danshenol B alleviates CPSP in mice by suppressing the PIK3CG/NLRP3 signaling pathway, elucidating its analgesic mechanism and highlighting its potential as a novel therapeutic candidate for CPSP.